USP14 is crucial for proteostasis regulation and α-synuclein degradation in human SH-SY5Y dopaminergic cells - Vignesh Srinivasan; Rabah Soliymani; Larisa Ivanova; Ove Eriksson; Nina Peitsaro; Maciej Lalowski; Mati Karelson; Dan Lindholm (Heliyon)
Ubiquitin specific protease-14 (USP14) is critical for controlling proteostasis disturbed in human disorders, including Parkinson's disease (PD). Here we investigated USP14 in the regulation of α-synuclein (α-syn) degradation via the proteasome and autophagy. α-Syn and pS129 α-syn were elevated in USP14 gene-deleted SH-SY5Y dopaminergic cells with decreased proteasome activity. However, autophagy and coordinated lysosomal expression and regulation pathways were elevated in USP14 lacking cells with higher levels of the transcription factor TFEB. There was an increase in reactive oxidative species (ROS) and elongated mitochondria in USP14 deficient cells and counteracting oxidative stress decreased α-syn levels. Phosphoproteomics revealed that USP14 is phosphorylated at residue S143 that reduces its binding to the proteasome. Re-expression of wild-type and phospho-mimetic S143D-USP14 mutant lowered ROS and α-syn levels in USP14 lacking cells. USP14 is a promising factor to consider in PD to target α-syn through its regulation of proteasomes and oxidative stress in dopaminergic neurons.